Receptor usage of Syncytin-1: ASCT2, but not ASCT1, is a functional receptor and effector of cell fusion in the human placenta - Štafl, Kryštof; Trávníček, Martin; Janovská, Anna; Kučerová, Dana; Pecnová, Ľubomíra; Yang, Zhiqi; Stepanec, Vladimír; Jech, Lukáš; Salker, Madhuri S; Hejnar, Jiří; Trejbalová, Kateřina (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Syncytin-1, a human fusogenic protein of retroviral origin, is crucial for placental syncytiotrophoblast formation. To mediate cell-to-cell fusion, Syncytin-1 requires specific interaction with its cognate receptor. Two trimeric transmembrane proteins, Alanine, Serine, Cysteine Transporters 1 and 2 (ASCT1 and ASCT2), were suggested and widely accepted as Syncytin-1 cellular receptors. To quantitatively assess the individual contributions of human ASCT1 and ASCT2 to the fusogenic activity of Syncytin-1, we developed a model system where the ASCT1 and ASCT2 double knockout was rescued by ectopic expression of either ASCT1 or ASCT2. We demonstrated that ASCT2 was required for Syncytin-1 binding, cellular entry, and cell-to-cell fusion, while ASCT1 was not involved in this receptor interaction. We experimentally validated the ASCT1-ASCT2 heterotrimers as a possible explanation for the previous misidentification of ASCT1 as a receptor for Syncytin-1. This redefinition of receptor specificity is important for proper understanding of Syncytin-1 function in normal and pathological pregnancy.
Keywords: fúze buněk; Pregnancy Proteins; Female; transportní systémy pro neutrální aminokyseliny; ženské pohlaví; Amino Acid Transport Systems, Neutral; genové produkty env; Placenta; antigeny CD98 - těžký řetězec; lidé; vedlejší histokompatibilní antigeny; těhotenství; Gene Products, env; Trophoblasts; endogenous retrovirus; transportní systém ASC pro aminokyseliny; Syncytin-1; těhotenské proteiny; viral receptor; Fusion Regulatory Protein 1, Heavy Chain; Amino Acid Transport System ASC; cell-to-cell fusion; Pregnancy; placenta; Cell Fusion; trofoblasty; Minor Histocompatibility Antigens; Humans